English for economics - Kissová, Oľga, 1966-; Bugárová, Antónia, 1981- (University of Žilina : EDIS-Editing Centre UNIZA, 2025)
This book introduces the JobLab concept through dynamic business simulations designed for Economics graduates. It focuses on English for Specific Purposes (ESP), strengthening real-world use of language in professional settings.The program builds entrepreneurial thinking and the key managerial skills while exploring five job-related topics.Students engage with interactive tools such as flashcards and quizzes, used in practical scenarios to solve tasksand challenges effectively. JobLab links theoretical learning with experience, supporting creativity and applied skills.It promotes professional expression, active listening, persuasive speaking, and confident communication at work